Monitoring technique for catalytic waste treatment by acoustic emission parameters - Vladimir L. Gaponov; Dmitry M. Kuznetsov (Advanced Engineering Research)
The work objective is to study issues of determining the hydrogen peroxide concentration. The task is to evaluate metrological aspects of the hydrogen peroxide decomposition. Alongside with a standard permanganatometric (analytical) method of determining the hydrogen peroxide concentration, a fairly new technique of the acoustic emission is considered. A new methodology of the problem solution developed by the authors is presented. The study has found that the hydrogen peroxide catalytic decomposition reaction is characterized by a strongly marked transient process at the initial stage. Further, the total number of pulses uniformly increases, and then the hydrogen peroxide concentration gradually decreases. The proposed method of monitoring the acoustic emission parameters shows high informativity and sensitivity. It is found that the spread in the experimental values obtained by the two methods is identical - 5 - 6% of the measured value.